Borneo Taste / Casianus Leticia Bansin... [et al.] - Bansin, Casianus Leticia; Abdul Rahman, Nur Azira; Jalit, Jalisius; Henry, Hillary Heaston; Muhmin, Satrinah (2016)
The name of our company is Borneo Taste. Our Restaurant will serve the food that use fish as our main ingredient in our menu. Our recipe made using our own ideas and come out with new taste of fish dishes. The nature of our business is partnership. Our restaurant located Borneo Taste Restaurant, Block B, Lot 14, Pekan Kundasang, 89308, Ranau, Sabah. We expect to start up our business on 18 January 2016. Our vision is to be one of the well known restaurants in the Borneo. Our products are sold to all ages, whether children or an adults. In running this business, we have 14 workers consists of General manager, Administration manager, Marketing manager, Operational Manager, Financial manager and our professional workers. Our future prospect of this business is to open as many branch and also promote our products as we can to earn more profit and expand our business in international level. There are 4 shareholders on this business. All the manager from all department also consist of the general manager contribute RM8,000 . Besides that, we also apply loan from Maybank Sdn. Bhd which is RM 37,165.